THE EFFECTIVENESS OF PRENATAL YOGA REDUCE PREGNANT WOMEN'S ANXIETY FACING CHILDBIRTH - Muthoharoh, Husnul; kurniawati, Indah; Ayu Asmarani, Nimas (Jurnal Ilmiah Kesehatan, 2024)
During pregnancy and before delivery, this fear often occurs in pregnant women. Anxiety is a feeling of worry, such as fear or uncertainty, as well as an unclear personal emotional condition about specific objects. The incidence of anxiety for primigravida mothers is 66.2% compared to multigravida mothers, which is 42.2%. Feelings of anxiety during pregnancy will have a negative impact on the growth and development of the fetus. Prenatal yoga helps the mind focus on pregnant women in regulating breathing techniques and provides comfort, security, calm and relaxation. This study aimed to determine the effectiveness of prenatal yoga in reducing the anxiety of pregnant women facing childbirth. The research design used was an experiment, purposive sampling with a sample of 32 third-trimester pregnant women—direct data collection using the STAI questionnaire instrument. The research results were analyzed using the Wilcoxson test. The results showed that all respondents experienced a decrease in their level of anxiety from moderate to mild after doing prenatal yoga. The results of the analysis obtained the value of Asymp.Sig. (2-tailed) 0.000 <0.05, meaning there is a correlation between the effectiveness of prenatal yoga in reducing anxiety for pregnant women facing labour. In conclusion, the study's results found that prenatal yoga can reduce the anxiety of pregnant women. Mothers should routinely do prenatal yoga so they do not experience anxiety during pregnancy.